Biomineralization improves the thermostability of foot-and-mouth disease virus-like particles and the protective immune response induced. Issue 47 (10th October 2019) - Du, Ping; Liu, Ronghuan; Sun, Shiqi; Dong, Hu; Zhao, Ruibo; Tang, Ruikang; Dai, Jianwu; Yin, Hong; Luo, Jianxun; Liu, Zaixin; Guo, Huichen
Abstract : Schematic description of immune activation of DCs of the thermostable biomineralized VLPs. Abstract : Virus-like particles (VLPs) are an ideal substitute for traditionally inactivated or attenuated viruses in vaccine production. However, given the properties of their native proteins, the thermal stability of VLPs is poor. In this study, calcium mineralization was used to fabricate foot-and-mouth disease virus (FMDV) VLPs as immunogenic core–shell particles with improved thermal stability. The biomineralized VLPs were stably stored at 24 °C and 37 °C for 13 and 11 days, respectively. Animal experiments showed that the biomineralized VLPs induced specific protective immunogenic effects, even after storage at 37 °C for 7 days. The biomineralized VLPs also effectively activated dendritic cells (DCs) to express high levels of surface MHC-II, costimulatory molecules, and proinflammatory cytokines. The DCs activated by the mineralized VLPs rapidly localized to the secondary lymphoid tissues and promoted the activation of the native T-cell population. These results suggest that the biomineralization of VLPs is an effective approach to vaccine production insofar as the mineralized shell provides an adjuvant effect which improves the immunogenicity of the VLPs. Biomineralization can also confer superior heat resistance on VLPs, an advantage in vaccine production. The successful development of thermally stable, biomineralized VLPs will reduce our dependence on cold storage and delivery.